PENGARUH PENGGUNAAN METODE DISCOVERY BERBASIS MEDIA REALITA TERHADAP HASIL BELAJAR MATAKULIAH KONSEP DASAR IPA 1 - Atmojo, Idam Ragil Widianto (Universitas Pendidikan Indonesia, 2015)
This study aims to determine how much influence the use of media-based discovery method's realities of the learning outcomes during the course Basic Concepts IPA 1 when compared to those taught using direct instruction-based Power Point (PPT). This research is a quantitative type of experiment using a quasi-experimental method (Quasi-Experimental Design). Experimental Design). Design research is the Control Group Pre-test Post-test. Populations of this study were all students of PGSD FKIP UNS second semester of academic year 2013/2014. Cluster Random Sampling is used in sampling. The technique of collecting data through observation, documentation, and testing. The data analysis technique used is the prerequisite test data analysis and hypothesis testing. For prerequisite test, including normality test with chip-square method and homogeneity test methods Bartlett. Based on the analysis of t test showed the t count t table (3.599 2.001), so that H0 is rejected. Thus there is a positive impact on learning outcomes of the course the basic concepts of science one-second semester students are taught using methods of discovery-based media reality. Conclusions This study is the result of learning the basic concepts of science subject 1 student taught by media-based discovery method's realities better than students taught by direct instruction-based power point.Keywords: discovery, media reality, learning outcomes, basic concepts IPA.